Autism Spectrum Disorder and IQ – A Complex Interplay - Wolff, Nicole; Stroth, Sanna; Kamp-Becker, Inge; Roepke, Stefan; Roessner, Veit (Frontiers in Psychiatry, 2022)
Autism Spectrum Disorder (ASD) is characterized as a very heterogeneous child-onset disorder, whose heterogeneity is partly determined by differences in IQ. Older epidemiological studies suggested that the IQ-related spectrum tends to be skewed to the left, i.e. a larger proportion of individuals with ASD have below average intelligence, while only few individuals with ASD may have an IQ above average. This picture changed over time with broadening the spectrum view. Within the present perspective paper, we discuss discrepancies in IQ profiles between epidemiological and clinical studies and identify potential underlying factors e.g. the influence of external factors, such as sample biases or differences in availability of autism health services. Additionally, we discuss the validity and reciprocal influences of ASD diagnostics and IQ measurement. We put the impact of these factors for diagnostic as well as care and support situations of patients into perspective and want to encourage further research to contribute to the conceptualization of "autism" more comprehensively including the IQ as well as to scrutinize broader circumstances, interacting factors and diagnostic requirements of given diagnoses in childhood as compared to adulthood.